Effect of induction chemotherapy on swallow physiology and saliva production in patients with head and neck cancer: A pilot study. Issue 4 (9th April 2014) - Mittal, Bharat B.; Pauloski, Barbara Roa; Rademaker, Alfred W.; Discekici–Harris, Muveddet; Helenowski, Irene B.; Mellot, Ann; Agulnik, Mark; Logemann, Jerilyn A.
Abstract: Background: No objective data are available to assess the potential damage induction chemotherapy alone contributes to swallowing physiology and salivary production in patients with locally and regionally confined head and neck cancer. Methods: Thirteen patients with head and neck cancer were evaluated preinduction and postinduction chemotherapy. Assessment included: (1) percentage of nutrition taken orally and food consistencies in diet; (2) videofluorographic swallow evaluation; (3) whole mouth saliva collection; (4) quality‐of‐life questionnaire; and (5) pain and oral mucositis scores. Results: All patients were able to consume most foods and took 100% of their nutrition orally both preinduction and postinduction chemotherapy. Although a number of swallow measures worsened, no statistically significant differences were observed in diet, quality of life measures, pain, or saliva weight, or in most temporal swallow measures. Pharyngeal residue decreased significantly after chemotherapy. Conclusion: Induction chemotherapy alone did not significantly negatively alter swallowing physiology and salivary secretion, although the trend was toward worsening in function. © 2014 Wiley Periodicals, Inc. Head Neck 37 : 567–572, 2015